2022
DOI: 10.3389/fcvm.2022.1071533
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology and molecular docking-based analysis of protective mechanism of MLIF in ischemic stroke

Abstract: ObjectiveThis study aimed to evaluate the potential mechanism by which Monocyte locomotion inhibitory factor (MLIF) improves the outcome of ischemic stroke (IS) inflammatory injury.MethodsPotential MLIF-related targets were predicted using Swiss TargetPrediction and PharmMapper, while IS-related targets were found from GeneCards, PharmGKB, and Therapeutic Target Database (TTD). After obtaining the intersection from these two datasets, the Search Tool for Retrieval of Interacting Genes/Protein (STRING11.0) data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…RBFOX1 is a splicing factor of Ca/calmodulin-dependent protein kinase II γ ( CAMK2G ), and its expression is reduced in patients with post-myocardial infarction (28) . Monocyte locomotion inhibitory factor ( MLIF ) protects against ischaemic stroke by lowering MAPK10 (JNK3) and decreasing proinflammatory cytokines (29) . The DLG2 gene encoding postsynaptic density protei n -93 (PSD-93) and its inhibition activates nuclear factor erythroid 2-related factor 2 (Nrf2)/antioxidant response element (ARE) antioxidant signalling in oxygen-glucose deprivation and reoxygenation (OGD/R)-exposed neurons (30) .…”
Section: Discussionmentioning
confidence: 99%
“…RBFOX1 is a splicing factor of Ca/calmodulin-dependent protein kinase II γ ( CAMK2G ), and its expression is reduced in patients with post-myocardial infarction (28) . Monocyte locomotion inhibitory factor ( MLIF ) protects against ischaemic stroke by lowering MAPK10 (JNK3) and decreasing proinflammatory cytokines (29) . The DLG2 gene encoding postsynaptic density protei n -93 (PSD-93) and its inhibition activates nuclear factor erythroid 2-related factor 2 (Nrf2)/antioxidant response element (ARE) antioxidant signalling in oxygen-glucose deprivation and reoxygenation (OGD/R)-exposed neurons (30) .…”
Section: Discussionmentioning
confidence: 99%
“…Through molecular docking techniques, AQP4 was pinpointed as one of the top ten central genes discovered in this study. Findings revealed that MLIF possesses anti-apoptotic properties and suppresses the expression of AQP4 protein, thereby playing a protective role in traumatic brain injury [ 155 ].…”
Section: Emerging Technologies and Future Directionsmentioning
confidence: 99%
“…Antisense oligonucleotides Bind to mRINA, prevent AQP4 functional protein formation, reduce edema if administered early [145] Minocycline Suppresses AQP4 expression post-TBI, protects BBB integrity, modulates astrocyte characteristics [146] Acetazolamide Inhibits CA, prevents AQP4 redistribution post-TBI, mitigates cytotoxic edema [147] miR-211-5p Regulates MMP9/AQP4 axis, therapeutic potential for TBI treatment by targeting this pathway [148] Trifluoperazine Reduces AQP4 accumulation, mitigates brain edema, reduces neurological severity post-TBI [149][150][151] Adenine dinucleotide phosphate oxidase 2 NOX2 inhibition reduces AQP4 levels, enhances cognitive function, reduces brain edema post-TBI [152] Hypertonic saline Reduces AQP4, TNFa, IL-1B levels, and brain water contact, suppresses apoptosis post-TBI [153] Monocyte locomotion inhibitor factor Reduces brain water content, suppresses AQP4 suppression, provides protection against TBI [154,155] Lentivirus-mediated AQP4 gene silencing Reduces AQP4 expression, mitigates brain edema, reduces neurological deficits and neuronal apoptosis post-TBI [156] Omega-3 polyunsaturated fatty acids Improve glymphatic clearance, reduce AB42 accumulation, protect BBB integrity post-TBI [162] Angiotensin II type 1 receptor Deficiency preserves BBB integrity, reduces AQP4 polarization, improves glymphatic function, and AB clearance post-TBI [158] Melatonin receptors Interaction with estrogen may reduce BBB permeability, influence AQP4 expression [160] Arginin and laminin Regulate BBB integrity and AQP4 polarization, important for astrocyte migration and plasticity [161] Future research should focus on developing specific inhibitors and modulators of AQP channels, particularly AQP4, to directly intervene in the edema formation process. Additionally, the exploration of gene silencing techniques, such as the use of antisense oligonucleotides, and the modulation of aquaporin expression through pharmacological agents or dietary supplements like Omega-3 PUFAs could provide new therapeutic avenues.…”
Section: Technology/approach Description Referencementioning
confidence: 99%